Minding menopause in patients with cognitive impairment: a patient's perspective and reflections on clinical practice - Elias Thomas; Petra Verdonk; Hanneke Rhodius-Meester; Majon Muller (BMC, 2023)
Abstract Many women experience impairment in cognitive function during perimenopause. These symptoms are often not attributed to perimenopause by women themselves, by family and friends, or by healthcare professionals. In this article, we present a case in which perimenopausal complaints were attributed to early dementia and discuss mechanisms contributing to the low level of awareness of perimenopausal symptoms amongst patients and clinicians. Stigma amongst women and healthcare professionals impairs the recognition of perimenopausal complaints, and consideration of treatment options by clinicians. We advocate raising awareness in patients and physicians with more education, and the incorporation of potential menopause-related symptoms in general clinical guidelines.